Adapted Fencing for Patients With Invasive Breast Cancer: The RIPOSTE Pilot Randomized Controlled Trial - Omorou, Abdou Y.; Peiffert, Didier; Rotonda, Christine; Van Hoye, Aurélie; Allado, Edem; Hily, Oriane; Temperelli, Margaux; Chenuel, Bruno; Hornus-Dragne, Dominique; Poussel, Mathias (Frontiers in Sports and Active Living, 2022)
Introduction Even if indications for mastectomy have been progressively reduced in loco-regional breast cancer (BC) treatment, the harmful effects of surgery are still numerous and can impact physical and psychological wellbeing of women. The RIPOSTE (Reconstruction, self-Image, Posture, Oncology, “Santé”-Health, Therapy, “Escrime”-Fencing) program aimed to propose adapted fencing to patients with BC. This study aims to investigate the effect and conditions of effectiveness of the RIPOSTE program. Methods and analysis This is a prospective randomized controlled trial including 24 patients with invasive BC who have just undergone surgery. The study will be proposed to the patient and if interested, the patient will be referred to a sports physician for a medico-sportive evaluation. At the end the evaluation, if the patient meets the inclusion criteria, she will be randomly assigned to one of the 2 groups based on a 1:1 principle: Early RIPOSTE group (receive one fencing session per week for 3 months immediately after their inclusion), Delayed RIPOSTE group (receive one fencing session per week for 3 months but within the 3 months following their inclusion). Patients will be included for 6 months with 3 follow-up times (0, 3, and 6 months) by a sport physician. The primary outcome is the evolution of quality of life score. Secondary outcomes are disability score, fatigue, anxiety-depression, cost-effectiveness and process evaluation. Ethics and dissemination The study protocol has been approved by a French ethics committee (CPP Sud Méditerranée IV, N°ID-RCB: 2020-A01916-33). Results will be submitted for publication, at scientific conferences and through press releases. Trial Registration NCT04627714.